EFEKTIVITAS METODE TALAQQI DALAM MENINGKATKAN KEMAMPUAN MENGHAFAL AL-QUR’AN ANAK USIA DINI - Susianti, Cucu (IKIP Siliwangi, 2016)
The purpose of the national education is mainly to mould a religious and God-fearing generation of human. One of the ways to achieve this is through the introduction of Al-Qur‟an during early childhood. Every Muslim is required to memorize the verses in Al-Qur‟an, at least some of the shorter Al-Qur‟an surah in Juz‘Amma, which is the 30th juz in Al-Qur‟an, because those are the surahs which is used during the prayer. Memorizing Al-Qur‟an is an activity that is very closely related to the work of memory in the brain. Therefore the methode used in memorizing Al-Qur‟an for children should be using methods appropriate for early childhood development. The purpose of this article is to discover the effectiveness of the talaqqi method in enhancing the ability to memorize Al-Qur‟an for early childhood. The relevance of this article lies in the importance of implementing Al-Qur‟an memorizing learning program which is suitable to the differentadolescent age groups. The method used in this article is literature study through examining a variety ofreading sources. This article will demonstrate the positive effect of the talaqqi method in enhancing theability to memorize Al-Qur‟an for adolescent.Keywords: Talaqqi method, Memorizing Al-Qur’an, Early childhood.